Dermatoglyph, somatotype and body composition in beach handball: Comparative study among different level of sportive qualification - Sena, J. E. A.; Gomes, A. L. M.; Mimbacas, A.; Ferreira, U. M. G. (Motricidade, 2012)
The aim of this study was to compare the dermatoglyph, somatotype and body composition at different level of qualification of Brazilian women's beach handball. This study was transversal, descriptive and comparative character. The sample consisted of n=32 athletes; (n=10) high performance (bi-champion of the world); (n=11) intermediary performance (compete national championships) and (n = 11) low performance (compete neighborhood tournaments and/or at most municipal). Was used the mean, standard deviation, minimum, maximum, MANOVA, one-way ANOVA, Kruskal-Wallis test, and Scheffe's post hoc test, significance level of p < .05.There was no difference (p > .05) for: A, L, W, D10, SQTL D10, SQTL e IMC, but difference to % G. There was a higher incidence of loop (L) and the formulas L>W, ALW, W> L, AL. The groups presented on average BMI eutrophic, with high, intermediary and low performance, presenting respectively 22.74kg/m², 23.70 kg/m² and 22.01 kg/m² with G% above values for the beach handball. The Somatotype was mesomorphic endomorph for all groups. Although the velocity has been the physical quality with greater genetic predisposition (high, intermediary and low performance respectively 71.0%, 54.0%, 83.0%), the sportive qualification was characterized by coordination, endurance, velocity and explosive strength, with high performance presenting better values than the others.